Illiquidity Premia in the Equity Options Market - Christoffersen, Peter; Goyenko, Ruslan; Jacobs, Kris; Karoui, Mehdi (Review of Financial Studies, 2018)
Standard option valuation models leave no room for option illiquidity premia. Yet we find the risk-adjusted return spread for illiquid over liquid equity options is 3.4% per day for at-the-money calls and 2.5% for at-the-money puts. These premia are computed using option illiquidity measures constructed from intraday effective spreads for a large panel of U.S. equities, and they are robust to different empirical implementations. Our findings are consistent with evidence that market makers in the equity options market hold large and risky net long positions, and positive illiquidity premia compensate them for the risks and costs of these positions. (JEL G12)